2017
DOI: 10.1097/olq.0000000000000628
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of a Smartphone-Based Electronic Reader of Rapid Dual Point-of-Care Tests for Antibodies to Human Immunodeficiency Virus and Treponema pallidum Infections

Abstract: Background Dual point of care tests for antibodies to human immunodeficiency virus (HIV) and Treponema (T.) pallidum allow for same-day testing and treatment and have been demonstrated to be cost-effective in preventing the adverse outcomes of HIV infection and syphilis. By recording and transmitting data as they are collected, electronic readers address challenges related to the decentralization of point of care testing. Methods We evaluated a smartphone-based electronic reader using 201 sera tested with tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Our results showed that the performance of the E-reader correlated well with visual inspection. Our findings are similar to what has previously been reported during a laboratory evaluation of the HRDR-200 E-reader 21. While the E-reader did not improve antibody detection in our study, the non-inferiority to visual inspection by trained technicians may mean that E-readers can improve case detection in areas without personnel trained in interpretation of rapid immunoassays.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results showed that the performance of the E-reader correlated well with visual inspection. Our findings are similar to what has previously been reported during a laboratory evaluation of the HRDR-200 E-reader 21. While the E-reader did not improve antibody detection in our study, the non-inferiority to visual inspection by trained technicians may mean that E-readers can improve case detection in areas without personnel trained in interpretation of rapid immunoassays.…”
Section: Discussionsupporting
confidence: 91%
“…One previous study evaluated the performance of the First Response HIV 1+2/Syphilis Combo Card Test in a laboratory setting and found sensitivity and specificity of 95.2% and 100%, respectively, for HIV antibodies, and 91.2% and 100%, respectively, for T. pallidum antibodies 21. Our results demonstrated similarly high sensitivities and specificities, but differ from those findings in that our study was performed in a clinical setting using venous whole blood instead of using stored sera in the laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…via automated RDT measurements (Box 3). This approach capitalises on mobile phone imaging38 or video capture39 to enable the quantitative40 assessment of results with the potential for geotagging41 and rapid transmission of results to healthcare systems42. Similarly, mobile phone-based microscopy43 is now gaining traction in detecting microscopic parasitic infections44, and is rapidly approaching that of laboratory based microscopes with a significantly reduced upfront cost.…”
Section: Developing Connected Point Of Care Infectious Disease Diagnomentioning
confidence: 99%